O que sabemos sobre a governança ambiental em áreas protegidas? : Tendências e direcionamentos - Santos, Henrique da Silva (2023)
Environmental governance can be defined as the interaction between structures, processes, and traditions that determine how power and responsibilities are exercised by stakeholders, for which various governance instruments can be used. Its use has grown in recent years, especially in protected areas. Here, our objective was to analyze the articles indexed in two databases – Web of Science and Scopus – on environmental governance in protected areas, to establish an overview of the studies worldwide. For this, scientometrics, a methodology linked to metrics, can trace scientific advances over time. Data were processed in software RStudio and Excel. Chloropleth maps were also prepared in the program QGIS 3.22.16. The study is divided into a literature review; study design, data collection, analysis, visualization, and interpretation. The search time interval was 1999-2022. As a result, 768 articles were in the two databases, distributed in 222 journals, being carried out by 2555 authors. The USA, United Kingdom, Australia, Canada, Brazil, Mexico, and Indonesia were the countries that most stood out in scientific production. As expected, most studies fall within the governance and methodological categories. The results indicate that the use of scientometric analysis proved to be important in identifying and monitoring research on environmental governance in protected areas. The evaluation of the knowledge produced is a necessity for all sectors that carry out research, as it is possible to infer new areas of investigation, as well as to determine and point out gaps in knowledge.